Left Sided Oesophageal Lung: A Diagnostic Challenge. (6th March 2013) - Sur, Amitava; Sardar, Syamal Kumar; Paria, Anshuman
Abstract : Bronchopulmonary foregut malformations (BPFMs) include a wide variety of malformations such as intralobar or extralobar pulmonary sequestration, foregut duplication cysts, and diverticula of the gastrointestinal or pulmonary tree (Srikanth et al., 1992). Those anomalies in which a tract between the respiratory and alimentary systems exists are termed communicating bronchopulmonary foregut malformations (CBPFMs). Most infants with CBPFMs suffer from respiratory distress, and an accurate diagnosis may be difficult to make at the patient's initial presentation. Herein we report such a case which posed a diagnostic challenge to us. This baby however survived and is doing well on a 2-year followup.